2022
DOI: 10.1108/jima-10-2021-0332
|View full text |Cite
|
Sign up to set email alerts
|

Religious affiliation and religiosity: do Islamic appeals in advertising lead to higher purchase intentions among Muslim consumers in Dubai?

Abstract: Purpose The purpose of this study was to investigate whether including an Islamic appeal in a culture-neutral product advertisement has a positive effect on consumer attitudes to the advertisement leading to higher purchase intentions while considering religious affiliation and religiosity as moderating factors of the relationship. Design/methodology/approach Conditional process analysis was applied to examine the mediation of the relationship between ad version and purchase intention through attitude to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Being religious influences all the decisions of an entrepreneur, and it reflects in their entrepreneurial activities. Religion may comprise of "spirituality" and "laws and regulations" and thus, it further produces a meaningful intention IJSSP 43,11/12 (Nickerson et al, 2022). Furthermore, researchers also assert that religion can be categorized into "spirituality" and "religiosity".…”
Section: Religiosity and Entrepreneurial Intentionmentioning
confidence: 99%
“…Being religious influences all the decisions of an entrepreneur, and it reflects in their entrepreneurial activities. Religion may comprise of "spirituality" and "laws and regulations" and thus, it further produces a meaningful intention IJSSP 43,11/12 (Nickerson et al, 2022). Furthermore, researchers also assert that religion can be categorized into "spirituality" and "religiosity".…”
Section: Religiosity and Entrepreneurial Intentionmentioning
confidence: 99%
“…Second, a recent studies on pro-environmental behaviour ( Bhuian et al, 2018 ; Soomro, 2019 ) suggested that the moderating role of Islamic religiosity should be considered in the context of the relationships between the antecedents of TPB and consumers’ purchase intentions towards eco-friendly products. Moreover, researchers in the fields of marketing and consumer behaviour agree that the concept of Islamic religiosity is significant in thoroughly explicating pro-environmental consumer behaviour ( Setyawati et al, 2020 ; Nickerson et al, 2022 ). However, very little research has been specifically concerned with demonstrating the role of religiosity in non-western contexts, i.e., Malaysia and Pakistan ( Wang et al, 2020a ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%